Sustainable Performance Improvement Model for MSME Human Resources Through Implementation Management Knowledge and Competence Entrepreneurship in Mediation Ability Digital literacy - Anggraeni, Anggun; Senen, Syamsul Hadi; Masharyono, Masharyono (Kontigensi : Jurnal Ilmiah Manajemen, 2025)
Micro business small and medium own great contribution to growth economy especially in developing countries such as Indonesia for example. Empowering MSMEs can become breakthrough in anticipate recession economy Where the number of MSMEs is increasing rise and have great contribution to gross domestic product (GDP), in 2023 MSMEs will reach 66 million units, an increase of 1.52% from year previously Where contribution its contribution to GDP reached 61% equivalent with Rp 9,580 trillion, then MSMEs can also absorb around 117 million power Work or 97% of power Indonesian work. However based on an international survey more 80 % of MSMEs in Asia closed in 2018 third they stand with various reason like lack of digitalization, competition company big , less market wide until with problem legality that is not complete . Then in support improvement quality of UMKM ministry Cooperatives and SMEs focus on performance business with one of the program that is digital transformation of MSMEs. Research This apply approach quantitative and use technique taking non-probability convenience sample (262 respondents). Partial Least Square Structural Equation Modelling (PLS-SEM) using SmartPLS4 was used. For analysis track and testing hypothesis. The explanatory power of the model is measured with R- squared and categorized as moderate. R2 value for Digital literacy significant (p 0. This means that the entire model of variable independent own validity or relevance adequate predictive in predict variation latent variables.